PENGARUH LITERASI KEUANGAN, KONTROL DIRI, DAN TEMAN SEBAYA TERHADAP PERILAKU MENABUNG SISWA SMK NEGERI DI WILAYAH JAKARTA BARAT - Achmad Faisal; Achmad Fauzi; Dwi Kismayanti Respati (Yayasan Education and Social Center, 2023)
This research aims to determine the Effect of Financial Literacy, Self-Control, and Peers on the Saving Behavior of Students of State Vocational High Schools, 11th-grade Accounting and Financial Institutions in Region II, West Jakarta. With an affordable population totalling 251 students, such as Vocational High School 45 Jakarta, Vocational High School 13 Jakarta, and Vocational High School 17 Jakarta. The sample in this study was 152 respondents with a proportional random sampling technique and Isaac and Michael Formula. The method of data collection is by questionnaire. The data analysis techniques are descriptive analysis, test analysis requirements, and hypothesis testing. The results of this study show that there is a positive and significant influence between financial literacy on saving behaviour, self-control on saving behaviour, and peers on saving behaviour. In addition to having a positive and significant effect simultaneously between financial literacy, self-control, and the saving behaviour of peers. In this investigation, the coefficient of determination was calculated to be 29.8%; the remaining percentage was affected by other aspects that did not investigate